Influential factors and classification of cultivated land fragmentation, and implications for future land consolidation: A case study of Jiangsu Province in eastern China. (November 2019) - Liu, Jing; Jin, Xiaobin; Xu, Weiyi; Sun, Rui; Han, Bo; Yang, Xuhong; Gu, Zhengming; Xu, Cuilan; Sui, Xueyan; Zhou, Yinkang
Graphical abstract: Highlights: Cultivated land fragmentation (CLF) possesses spatial-scale characteristics aiming at different social groups. A new index system including the attributes of farmland in natural, spatial and utilization is created for CLF assessment. Spatial differentiation characteristics and influencing factors of CLF is analyzed. A framework of zoning scheme for CLF management is proposed to guide the land consolidation practices and diminish the CLF. Abstract: Cultivated land fragmentation (CLF) is one of the main obstacles hindering the development of agricultural modernization and mechanization. Systematically exploring the general distribution characteristics, influential factors and classification of CLF are of great significance for improving regional agricultural production capacity, promoting resource conservation and intensive use, and ensuring national food security, especially at the regional scale. In this study, we established a new conceptual index system using multivariable linear regression, geographical detectors, and magic cube model for CLF assessment as well as an analysis of the spatial differentiation characteristics, driving mechanism and management zoning trade-off of CLF in Jiangsu Province in eastern China based on multi-source data characterizing geographic, land-use and socio-economic information. The results showed that the connotation of CLF has spatial-scale characteristics due to the differences in functions positioning of cultivated land resources in macro-social security and micro-livelihood maintenance. At the national/regional scale, CLF mainly covers the natural (resource), spatial and utilization attributes of cultivated land. Based on this, the CLFI in Jiangsu presents a spatial pattern that gradually increases from north to south, with significant spatial differences. Besides, the CLFI within built-up areas is significantly higher than that outside built-up areas, and its fractal dimensions both within and outside the urban planning built-up areas show the spatial pattern of "spatial distribution > resource endowment > convenience of utilization". Furthermore, average plot size, the proportion of industry and service industry, gross domestic product, slope, grain output, and plot distance from town are the dominant factors driving the spatial differentiation of CLF, with the influence power ( q ) is 0.472, 0.204, 0.133, 0.129, 0.097 and 0.084, respectively. Location conditions and socio-economic activities have significant effects on the spatial differentiation of CLF within the built-up areas while highlighting the role of rural settlements outside urban built-up areas on CLF. Finally, we propose a two-level zoning system for diminishing the CLF and optimizing the utilization of cultivated land resources in Jiangsu based on influencing factors and fragmentation characteristics. The findings of this study will assist the government in developing appropriate regional context and land consolidation policies and coping strategies to CLF and food insecurity issues, and achieve sustainable development goals.